"a massive colonial experiment": New Zealand architecture in the 1840s - McCarthy, Christine (Architectural History Aotearoa, 2014)
It is more than obvious to say that the signing of the Treaty was the big event of the 1840s. The initial Treaty signing at Waitangi on 6 February 1840 by Lieutenant-Governor William Hobson, representing the British Crown, and "about 45 Maori chiefs" has become a defining moment in New Zealand’s history, but, as Smith notes, [o]nly recently has the Treaty of Waitangi become central to national life ... Hastily devised at the time, the treaty sheets have become a national monument: they mean different things to different groups but have had an evolving official interpretation placed upon them. The Treaty "is the basis of the Crown’s authority and legitimised European settlement in New Zealand," but important differences between the English version and the Māori version (which most Māori signed) include differences in the translations of article one (the cession of sovereignty vs "te kāwanatanga katoa" (governorship)), and silence in the te reo Māori text "on the Crown right of pre-emption. It promised the Queen "hokonga" - the buying and selling of land that Maori were willing to part with - but not exclusively, nor even as the highest priority.